Concepções sobre trabalho elaboradas por usuários de saúde mental envolvidos em projetos de inserção laboral - Lussi, Isabela Aparecida de Oliveira; Pereira, Maria Alice Ornellas [UNESP] (My University, 2014)
The present paper chose like investigation focus the work developed by users of mental health services in workshops of income generation or in social cooperatives. The aim was to identify the conception of work formed by the users. This study has involved fi fteen users. The free observation technique, a semistructured interview and a document searching were used in order to gather data. The empiric material was submitted to Thematic Analysis. The analysis of the material was based on the theoretical concepts of the Solidarity Economy and Deinstitutionalization. The results showed that on the conception of the participants of this study work is an important tool for the social emancipation of the people promoting self-knowledge and self-confi dence. It is important to mention the importance of the view of the social actors who are compromised directly with the laboral insertion.

O presente estudo elegeu como foco de investigação o trabalho desenvolvido por usuários de serviços de saúde mental em ofi cinas de geração de renda ou em cooperativas sociais. Objetivouse identifi car as concepções acerca do trabalho elaboradas pelos mesmos. Participaram do estudo quinze usuários. Para a coleta de material, utilizou-se a técnica da observação livre, entrevista semi-estruturada e busca documental. O material empírico foi submetido à Análise Temática. A análise do material foi subsidiada pelos pressupostos teóricos da Desinstitucionalização e da Economia Solidária. Os resultados mostraram que na concepção dos participantes o trabalho é uma importante ferramenta para a emancipação social das pessoas e um recurso que promove o autoconhecimento e a auto-realização. Aponta-se a importância de se considerar a opinião dos atores sociais diretamente comprometidos com a inserção laboral.
Conceptions about the work established by users of mental health services involved in laboral insertion projects
Keywords: Mental health; Rehabilitation; Rehabilitation, vocational/manpower; Sheltered workshops; Manpower; Work; Income; Saúde mental; Reabilitação; Reabilitação vocacional/recursos humanos; Oficinas de trabalho protegido/recursos humanos; Trabalho/psicologia; Renda